2003
DOI: 10.1034/j.1600-0765.2003.00687.x
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases and their inhibitors in gingival mast cells in persons with and without human immunodeficiency virus infection

Abstract: The chronically inflamed periodontal lesions in the present study appeared with little evidence of mast cell degranulation. The results show, however, that mast cells in inflamed gingiva have the potential to degrade extracellular matrix if appropriately triggered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
49
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 63 publications
(110 reference statements)
5
49
0
2
Order By: Relevance
“…This finding effectively confirmed the same finding of an increase in the mast cell population in NDV infection. The result was consistent with previous studies (Hattori et al, 1989;Chen et al, 2000;Naesse et al, 2003) showing that tryptase was largely within mast cells. Besides tryptase, a number of mediators released during mast cell degranulation, such as histamine and tumour necrosis factor, can also contribute to innate defence (Gonzalez-Espinosa et al, 2003;Dawicki & Marshall, 2007;Pejler et al, 2007).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This finding effectively confirmed the same finding of an increase in the mast cell population in NDV infection. The result was consistent with previous studies (Hattori et al, 1989;Chen et al, 2000;Naesse et al, 2003) showing that tryptase was largely within mast cells. Besides tryptase, a number of mediators released during mast cell degranulation, such as histamine and tumour necrosis factor, can also contribute to innate defence (Gonzalez-Espinosa et al, 2003;Dawicki & Marshall, 2007;Pejler et al, 2007).…”
Section: Discussionsupporting
confidence: 83%
“…Such potential roles include the ability to act as antigenprocessing and presenting cells, although this function so far has been demonstrated primarily in vitro (Eager et al, 1989;Frandji et al, 1993Frandji et al, , 1998Fox et al, 1994) or by the adoptive transfer of antigen-treated mast cells in vivo (Villa et al, 2001). Mast cells also have the potential to influence the migration, maturation, and/or function of dendritic cells (Caron et al, 2001;Cumberbatch et al, 2001;Stoitzner et al, 2001) and to influence the biology of other cell types that contribute to these responses, including T cells and B cells (Mekori & Metcalfe, 1999;Nakajima et al, 2002;Sayama et al, 2002;Okumura et al, 2003). In this study we observed an increased ratio of mast cells in the proventriculus, duodenum, jejunum and caecal tonsil.…”
Section: Discussionmentioning
confidence: 99%
“…The secreted inflammatory mediators participate in angiogenesis, tissue remodeling and wound healing, which include both degradation and synthesis of tissue components. Among these, nitric oxide (NO) (Bridi et al 1997) and matrix metalloproteinases (MMPs) (Naesse et al 2003;Di Girolamo et al 2006;Yoshinori et al 2007) have been strongly correlated with periodontal diseases (PDs), since they are the major players in collagen breakdown during periodontal tissue destruction (Hannas et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…The increase in the number of mast cells in cervical DOI: 10.5114/ceji.2012.32729 lymph nodes of HIV-positive men, as compared with healthy subjects, were observed [11], and a significantly higher mast cell count were found in the chorionic epithelium of the uterine cervix of HIV-infected women than of non-HIV-infected [12]. Also, the gingival tissue of HIV-1-positive patients with chronic marginal periodontitis as well as healthy gingiva displayed higher mast cell density in comparison with non-infected counterparts [13,14]. These findings could suggest that mast cells are directly or indirectly affected by HIV-1 and associated with infection aftermaths, including AIDS progression.…”
mentioning
confidence: 79%